UPAYA PENINGKATAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DALAM METODE PEMBERIAN TUGAS DI KELAS IV SDN INPRES 3 TALISE - A. Ardiansyah; Sitti Nadirah (ISTIQRA, 2014)
This study aims to improve students' learning achievement. on the subject of Islamic education through giving a class assignment method at IV SDN Inpres 3 Talise Palu. This research employed class action research conducted in two cycles. The stages of this research include the planning, action, observation and reflection. In this research, the data obtained include the observation activities of teachers and student activity by using sheets observation and the students' learning achievement were taken from the test. The results showed that in the first cycle the activity of students is in the category sufficient assessment and teacher activity is in the category of good judgment. In the second cycle, the average activity of students and teachers have been included in the category of very good assessment. As for the students' learning achievement in the first cycle of students' classical absorption reached 70.47%, while in the second cycle of the students' classical absorption has reached 88.86%. So it can be concluded that learning by giving a class assignment method can improve students' learning achievement in subjects of Islamic education